Pengaruh Penggunaan Multimedia Interaktif Berbasis Adobe Flash terhadap Peningkatan Prestasi Belajar Tema 5 Anak Tunagrahita Ringan Kelas 5 di SLB Negeri Surakarta Tahun Pelajaran 2016/2017 - Arfani, Fariz Riza (Indonesian Journal of Disability Studies, 2017)
The aim of this research is to determine the effect of the use of adobe flash based multimedia towards the increase of thematic learning achievement of five 5th graders with light intellectual disability in SLB Negeri Surakarta, academic year 2016/2017.This research using quantitative approach with One-group pretest-posttest design pre-experimental design. The subjects involved in this research were five 5th graders with light intellectual disability in SLB Negeri Surakarta. Data is colleted using a multiple choice objective tests. Data analyzed using non-parametric statistics through Wilcoxon Sign Rank test with the help of a software namely SPSS 23. Based on the analysis of descriptive data obtained the average score as much as 52.00 in the pretest and 82.00 in the posttest.The non-parametric statistics results of Wilcoxon Sign Rank Test note that the value of Z values = -2.041 with Asymp Sig (2-tailed) = 0,041 is smaller than a predetermined significance level or 0.041 < 0.05, so the alternative hypothesis is accepted and the null hypothesis is accepted. Based on the analysis result of this research we can conclude that the use of adobe flash based interactive multimedia affect the achievement of thematic learning towards five 5th graders with light intellectual disability in SLB Negeri Surakarta academic year 2016/2017.